PENINGKATAN KUALITAS PRAKTIK MENGAJAR GURU MELALUI PENELITIAN TINDAKAN KELAS BERBASIS REFLEKSI PEMBELAJARAN DI SDIT AS SABIQUUN - Noor Azida Batubara; Syifa Alya Rafidah; Mutmainnah Mutmainnah; Sausan Asy Syifa Putri (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to improve quality of teachers’ instructional practices through Classroom Action Research based on reflective teaching practices at SDIT As Sabiquun. The research was motivated by preliminary observations indicating that teachers’ instructional practices had not been optimally implemented, as reflected in limited instructional variation, inconsistent lesson implementation, and insufficient reflective evaluation of classroom teaching. This study employed a qualitative approach using a Classroom Action Research design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through classroom observations, field notes, teacher reflections, and instructional documentation. The data were analyzed qualitatively by examining changes in teachers’ instructional practices across each cycle. The findings indicate that the systematic implementation of reflective teaching practices contributed to noticeable improvements in the quality of teachers’ instructional practices. This study highlights the importance of reflective based action research as a practical approach for fostering continuous improvement in classroom teaching